Sosialisasi Pasar Modal Sebagai Alternatif Investasi Pada Masyarakat Desa Glonggong Kecamatan Dolopo Kabupaten Madiun - Mutmainah .; Siti Wardani Bakri Katti (Universitas Merdeka Madiun, 2021)
This social dedication is carried out to increase public awareness about investing in capital market. Investment is not only deposit or gold, but also investments can be shares. Share investment is the same as owning a company. Knowledge about investment in capital market very important for socialized to public, specially social of Madiun because this share investment result more profitable return than other investment type. So it can increase economy of Madiunâ€™s and more manage their financial. This social dedication use lecture and discussion method. This activity provide consultastion clinik to public in unlimited time range. The participants consisted of 35 men, women, men and women young. This activity will doneÂ in Balai Desa Glonggong office in subpdistrict Dolopo, Madiun district. Presented theory in this activity were knowledge about capital market, its strength and weakness, its risks, how to be investor, and role of Galeri Investasi BEI Economyc Faculty, Madiun Merdeka University. From this activity there are 10 people to be investor in capital market. This achievements very satisty because it is more targeted.